Hybrid design based on wire and arc additive manufacturing in the aircraft industry - Chen, Jian (Cranfield University, 2012)
Wire and Arc Additive Manufacturing (WAAM) is a developing rapid prototyping and manufacturing technology which allows the production of large custom-made metal parts with high deposition rates, a major concern of the aircraft industry. Despite this, there is little research on the design method and application of WAAM technology in the aircraft industry. The overall research aim is to develop a step-by-step design method to create and assess hybrid design solutions based on WAAM technology. The main objectives are to: (i) analyse existing design methods and software tools; (ii) collect and analyse technical data about aircraft structure design and WAAM process; (iii) develop a hybrid design method based on WAAM technology; (iv) validate the developed design method through industrial case studies. These four objectives were achieved through the adoption of a four-phase research methodology. A hybrid design method was developed based on mature design models such as the VDI 2221model, BS 7000 design model and Pahl and Beitz’s design model and required prior knowledge of WAAM technology and aircraft structure design. This design method includes a hybrid design model and a WAAM feature based design guideline which enables the designers to create hybrid design solutions step by step and assess the proposed solutions by using the evaluation matrix chart. Hybrid design in this research encompasses design for hybrid manufacturing processes, which means that an object is to be designed partly made from prefabricated or off-the-shelf parts and partly added by WAAM process. Furthermore, Finite Element Analysis is introduced in the design method to check the performance of the preliminary design and the final design. Three case studies were carried out to verify the developed hybrid design method. The integral panel, a typical structure in aircraft, demonstrates the significant cost advantage of WAAM technology. The pylon frame and forward fitting are the structural parts provided by the Chinese aircraft industry. It shows that the cost of the final design is significantly lower than that of the preliminary design. In addition, topology optimisation is applied to achieve lower weight. The hybrid design method is validated through academic experts and industrial experts. This research project has contributed to an effective design method based on WAAM technology in the aircraft industry.
Keywords: Wire and Arc Additive Manufacturing (WAAM); Hybrid design method; Aircraft industry; Evaluation